Impact of Firm Specific and Macro-Economic Factors on the Level of Underpricing of Initial Public Offerings (IPOs) : Evidence from the Indian Market - Pandey, Aprajita; Pattanayak, J. K. (Indian Journal of Finance, 2018)
The purpose of this paper was to examine the impact of firm specific and macro-economic factors on the level of underpricing of firms going for initial public offerings (IPOs) in the National Stock Exchange, India. We considered firms that went for IPOs on the National Stock Exchange during the period from 1999-2016, which was further segregated to quarterly observations. Both traditional method and market adjusted abnormal rate of returns (MAAR) methods were used to gauge underpricing. The study found that among the firm specific variables, issue price and firm age were significant in influencing the level of underpricing. Inflation, market volatility, market returns, and economic activity had greater explanatory power than other macro-economic variables on underpricing. The study contributes to the vast literature of determinants of underpricing as most of the study focused on firm-related factors only; this study has given some insights on the role of macro-economic factors to explain underpricing.